2020
DOI: 10.3389/fnhum.2020.583579
|View full text |Cite
|
Sign up to set email alerts
|

Crossed Corticospinal Facilitation Between Arm and Trunk Muscles Correlates With Trunk Control After Spinal Cord Injury

Abstract: Objective: To investigate whether crossed corticospinal facilitation between arm and trunk muscles is preserved following spinal cord injury (SCI) and to elucidate these neural interactions for postural control during functional arm movements. Methods: Using transcranial magnetic stimulation (TMS) in 22 subjects with incomplete SCI motor evoked potentials (MEPs) in the erector spinae (ES) muscle were examined when the contralateral arm was at rest or performed 20% of maximal voluntary contraction (MVC) of bice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 57 publications
4
18
0
Order By: Relevance
“…Our findings therefore inform a more comprehensive understanding of the basic principles of human motor control related to the arm-trunk neural interaction. Taken together, these results may also suggest that functional movement synergy oriented training is crucial in rehabilitation to strengthen arm-trunk interactions as a way for improving functional performance after neurological impairments such as spinal cord injury Chiou and Strutton, 2020).…”
Section: Significance Of Corticospinal Remote Facilitationmentioning
confidence: 77%
See 4 more Smart Citations
“…Our findings therefore inform a more comprehensive understanding of the basic principles of human motor control related to the arm-trunk neural interaction. Taken together, these results may also suggest that functional movement synergy oriented training is crucial in rehabilitation to strengthen arm-trunk interactions as a way for improving functional performance after neurological impairments such as spinal cord injury Chiou and Strutton, 2020).…”
Section: Significance Of Corticospinal Remote Facilitationmentioning
confidence: 77%
“…Our work has several limitations that should be noted. First, some previous studies investigating interactions between trunk and upper-limb muscles have examined contralateral side trunk muscles to the contracted arm to elicit MEP responses (Chiou et al, 2018;Chiou and Strutton, 2020;Davey et al, 2002), while we chose to investigate the ipsilateral side in the current study. Davey et al, (2002) previously reported that ES muscle activity in the contralateral side to contracted arm was increased when arm muscle contractions during shoulder abduction were increased, while that of ipsilateral side was not affected considerably.…”
Section: Limitationsmentioning
confidence: 99%
See 3 more Smart Citations